Investigating the breast cancer screening–treatment–mortality pathway of women diagnosed with invasive breast cancer: Results from linked health data. (30th November 2021) - Li, Ming; Reintals, Michelle; D'Onise, Katina; Farshid, Gelareh; Holmes, Andrew; Joshi, Rohit; Karapetis, Christos S.; Miller, Caroline L.; Olver, Ian N.; Buckley, Elizabeth S.; Townsend, Amanda; Walters, David; et al.
Abstract: Objective: To examine the screening–treatment–mortality pathway among women with invasive breast cancer in 2006–2014 using linked data. Methods: BreastScreen histories of South Australian women diagnosed with breast cancer ( n = 8453) were investigated. Treatments recorded within 12 months from diagnosis were obtained from linked registry and administrative data. Associations of screening history with treatment were investigated using logistic regression and with cancer mortality outcomes using competing risk analyses, adjusting for socio‐demographic, cancer and comorbidity characteristics. Results and conclusion: For screening ages of 50–69 years, 70% had participated in BreastScreen SA ≤ 5 years and 53% ≤ 2 years of diagnosis. Five‐year disease‐specific survival post‐diagnosis was 90%. Compared with those not screened ≤5 years, women screened ≤2 years had higher odds, adjusted for socio‐demographic, cancer and comorbidity characteristics, and diagnostic period, of breast‐conserving surgery (aOR 2.5, 95% CI 1.9–3.2) and radiotherapy (aOR 1.2, 95% CI 1.1–1.3). These women had a lower unadjusted risk of post‐diagnostic cancer mortality (SHR 0.33, 95% CI 0.27–0.41), partly mediated by stage (aSHR 0.65, 95% CI 0.51–0.81), and less breast surgery (aSHR 0.78, 95% CI 0.62–0.99). Screening ≤2 years and conserving surgery appeared to have a greater than additive association with lower post‐diagnostic mortality (interaction term SHR 0.42, 95% CI 0.23–0.78). The screening–treatment–mortality pathway was investigated using linked data.